The potential of soil amendment with insect exuviae and frass to control the cabbage root fly - Wantulla, Max; Zadelhoff, Kristian; Loon, Joop J. A.; Dicke, Marcel (Journal of applied entomology (1986), 2023)
Reliable options to control the cabbage root fly, Delia radicum L., are lacking in many countries as restrictions on insecticide use have tightened due to environmental concerns. Although microbial control agents are often considered as a sustainable alternative, their application in agriculture is constrained by inconsistent efficacy owing to low field persistence. To stimulate naturally occurring beneficial microbes, soil amendment with the residual streams of insect production has been suggested as an alternative to synthetic fertilization and a new approach to microbial crop protection. In a set of greenhouse experiments, exuviae and frass of black soldier fly larvae, Hermetia illucens L., house crickets, Acheta domesticus L. and exuviae of mealworms, Tenebrio molitor L., were added to soil from an organically managed field. Exuviae and frass treatments were compared to treatments with synthetic fertilizer. Brussels sprouts, Brassica oleracea L., plants were grown in amended soil for 5 weeks before being infested with cabbage root fly larvae. Insect and plant performance were assessed by recording cabbage root fly survival, biomass and eclosion time and seed germination and plant biomass, respectively. Whereas soil amendment with black soldier fly frass or exuviae reduced cabbage root fly survival and biomass, respectively, amendment with house cricket or mealworm residual streams did not negatively affect root fly performance. Furthermore, seed germination was reduced in soil amended with house cricket exuviae, while amendment with either residual stream derived from black soldier fly larvae or house crickets resulted in lower plant shoot biomass compared with the synthetic fertilizer treatment. Amending soil with black soldier fly residual streams could become a novel and low‐cost tool to be integrated in cabbage root fly management programmes, especially where methods currently available are insufficient. Therefore, the mechanisms underlying the effects of insect‐derived soil amendments described here should be the focus of future research.